Penggunaan Model Pembelajaran Artikulasi dalam Meningkatkan Hasil Belajar Siswa di SMPN 2 Pontang - Irfan Anshori; Alvi SA Putri; Ainul Qonitah (Muróbbî: Jurnal Ilmu Pendidikan, 2024)
This research aims to measure the use of the articulation learning model on student learning outcomes at SMP Negeri 2 Pontang. This research method uses quantitative methods; using a descriptive approach. The research results explain that the articulation learning model helps teachers in the learning process. The stages of this learning model are very systematic; starting from delivering the material to delivering the material; Benefits of using articulation models; produce students who are independent, dare to appear independent. The advantages of the articulation learning model; all students are involved, train student readiness, train student understanding and increase student participation. Lack of model articulation; requires a lot of time, is suitable for certain materials, the material obtained is small. Analysis of the Articulation Model on Learning Outcomes shows that the coefficient index rxy = 0.44 is between (0.40-0.70). This means that the Articulation Model and learning outcomes have a moderate correlation. The results of the significance test show that tcount = 4.4389 > ttable = 9.48. This means there is a significant positive correlation between the articulation model and learning outcomes. The contribution of the articulation model to learning outcomes is 20.22%. Tujuan penelitian ini untuk mengukur penggunaan model pembelajaran artikulasi pada hasil belajar siswa di SMP Negeri 2 Pontang. Metode penelitian ini menggunakan metode kuantitatif; dengan menggunakan pendekatan deskriptif. Hasil penelitian menjelaskan bahwa model pembelajaran artikulasi membantu guru dalam proses belajar. Tahapan model pembelaajran ini sangat sistematis; mulai dari penyampaian materi hingga penyimpulan materi; Manfaat penggunaan model artikulasi; menghasilkan siswa yang mandiri, berani tampil mandiri. Kelebihan model pembelajaran artikulasi; semua siswa terlibat, melatih kesiapan siswa, melatih daya serap pemahaman siswa dan meningkatkan partisipasi siswa. Kekurangan model artikulasi; membutuhkan waktu yang banyak, cocok untuk materi tertentu, materi yang didapat sedikit. Analisis Model Artikulasi pada Hasil Belajar menunjukan indeks koefesien rxy = 0,44 berada antara (0,40-0,70). Ini berati Model Artikulasi dengan hasil belajar terdapat korelasi yang sedang. Hasil uji signifikansi diketahui bahwa thitung = 4,4389 > ttabel = 9,48. Ini berati terdapat korelasi positif yang signifikan antara model artikulasi dengan hasil belajar. Kontribusi model artikulasi pada hasil belajar adalah 20,22%.